2013
DOI: 10.1186/1471-230x-13-74
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter comparison of PEG-IFN α2a or α2b plus ribavirin for treatment-naïve HCV patient in Korean population

Abstract: BackgroundTwo recent Italian studies suggested that Pegylated-interferon (PEG-IFN) alfa-2a achieves a higher sustained virological response (SVR) rate than PEG-IFN alfa-2b. We intended to compare the efficacy and safety of PEG-IFN alfa-2a with those of PEG-IFN alfa-2b in Korean patients with chronic hepatitis C virus (HCV).MethodsThis retrospective, multi-center trial was conducted on 661 treatment-naïve chronic HCV patients. Patients received PEG-IFN alfa-2a (180 μg/week; n=402) or PEG-IFN alfa-2b (1.5 μg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
4
18
1
Order By: Relevance
“…These results were better than those reported in Western studies (13% to 33% for genotype 1/4 and 31% to 57% for genotype 2/3)8,1719 and in small Korean studies (21% to 24% for genotype 1 and 33% to 53% in non-1 genotypes) 20,21. In addition, SVR rates in the current study reached 67% among patients without cirrhosis with HCV genotype 1 and 86% in those with non-1 genotypes, also better results compared to large-scale Western studies (57% to 60% for genotype 1 and 76% for non-1 genotype groups),8,22 but similar to other Korean data (74% for HCV genotype 1 and 83% in genotype non-1) 11…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results were better than those reported in Western studies (13% to 33% for genotype 1/4 and 31% to 57% for genotype 2/3)8,1719 and in small Korean studies (21% to 24% for genotype 1 and 33% to 53% in non-1 genotypes) 20,21. In addition, SVR rates in the current study reached 67% among patients without cirrhosis with HCV genotype 1 and 86% in those with non-1 genotypes, also better results compared to large-scale Western studies (57% to 60% for genotype 1 and 76% for non-1 genotype groups),8,22 but similar to other Korean data (74% for HCV genotype 1 and 83% in genotype non-1) 11…”
Section: Discussionsupporting
confidence: 86%
“…Although some Korean studies have reported relatively higher SVR rates in patients with HCV genotype 1 and non-1 genotypes compared to Western studies,11,12 the reasons for these improved responses have not been clearly delineated, and the response rate in cirrhotic patients remains uncertain. Some Western studies demonstrated that successful antiviral treatment in patients with CHC halted progression of hepatic fibrosis, but the risk of hepatocellular carcinoma remained even after achieving SVR 8,13.…”
Section: Introductionmentioning
confidence: 97%
“…Asconi, Rumi and Awad found that peginterferon alpha-2a was superior to peginterferon alpha-2b (35)(36)(37). However, in other studies carried out by McHutchison et al (38) and Jin et al (39), no difference was found between peginterferon alpha-2a and 2b in terms of SVR. In two studies conducted in GT 1 patients in Turkey, no difference was found between two peginterferons.…”
Section: Discussionmentioning
confidence: 90%
“…After a manual review, 118 duplicates and 650 studies irrelevant to our objectives were excluded, and 134 studies remained for further screening. Applying the inclusion and exclusion criteria, a total of 19 studies (four randomized control trials [RCTs], [14][15][16][17] ten meta-analysis studies, [18][19][20][21][22][23][24][25][26][27] three nonrandomized intervention studies, [28][29][30] one cross-sectional study, 31 and one cohort study 32 ) were included for the updated studies for this review (Table 1). Additionally, eight RCTs were also included in this review that were published during the study period of Chou et al 13 and met the inclusion/exclusion criteria, but were not reviewed by them.…”
Section: Methodsmentioning
confidence: 99%
“…Another retrospective multicenter trial conducted in Korea discovered that PEG-IFN alfa-2a and PEG-IFN alfa-2b had similar effects on SVR and adverse events rate, even after controlling for age, HCV viral load, and hepatic fibrosis. 29 A meta-analysis study, Flori et al, 18 investigated eleven randomized and 15 nonrandomized trials to evaluate the effectiveness of PEG-IFN alfa-2a vs PEG-IFN alfa-2b. 18 This study suggested that PEG-IFN alfa-2a plus RBV was more effective than PEG-IFN alfa-2b plus RBV, especially in genotype 1 or 4 HCV patients.…”
Section: Studies Other Than Rcts Dual Therapymentioning
confidence: 99%